Long‐term structural changes and outcomes of implants in particulate cellular bone and marrow reconstructed jawbone. (19th February 2019) - Matsuo, Akira; Hamada, Hayato; Takahashi, Hidetoshi; Chikazu, Daichi
Abstract: Background: Association between long‐term structural changes of grafted bone and outcomes of the implants is not clear. Purpose: Morphometrical measurements and implant success were analyzed in subjects of particulate cellular bone and marrow (PCBM) reconstruction of the jawbone. Materials and Methods: Subjects were 30 implants in 13 patients from a series of 24 PCBM reconstruction cases. The cortical bone thickness and cancellous computed tomography (CT) radiodensity values were retrospectively analyzed from the CT data of 27 subjects. The cumulative success rate of the implants in the PCBM reconstructed cases (pure graft) was compared with that of 127 implants of 56 native bone cases and 42 implants of 28 bone augmentation (partial graft) cases. Results: In areas of PCBM reconstruction, cancellous CT radiodensity values were significantly high immediately after the surgery, and subsequently the values became stable. Cortical thickness was significantly increased, but did not reach that of native bone. Implant success rates were statistically not different ( P = 0.783) between the native bone (91.3%), the partially grafted bone (95.2%), and the PCBM reconstructed bone (93.3%). Conclusion: Implants in pure grafted bone are mainly supported by cancellous bone, because cortical thickness remained thin for a long period of time.